Angiomyofibroblastoma of the Vulva - G Shilpa; Shivani Sharma; S R Raja Parthiban; Uzma Khan (Wolters Kluwer Medknow Publications, 2022)
Angiomyofibroblastoma (AMF) is a rare benign soft-tissue tumor that most frequently affects the lower genital tract of young to middle-aged women. It mainly consists of two components: stromal cells and prominent vasculature. Clinically, it is usually asymptomatic and resembles Bartholin's cyst. Although it is a benign tumor, cases with recurrence and sarcomatous transformation have been reported. Due to the overlapping of histopathological picture, diagnostic perplexity often arises between AMF and aggressive angiomyxoma (AAM). AMF being benign in nature is treated by local excision, whereas AAM is a more infiltrative lesion that has a higher tendency for local recurrence.